POLA DAKWAH INTERNAL KELUARGA INTI PADA ANAK PESISIR PANTAI DI SINJAI - Syamsuddin AB (Jurnal Dakwah Tabligh, 2022)
This study aims to analyze and describe the polarization of the nuclear family's internal propaganda in educating children from the religious aspect. Polarization is carried out by nuclear families as an effort to form quality coastal children based on faith and taqwa. In this type of qualitative research, data collection techniques are natural settings (natural conditions) in addition to collecting descriptive data, in-depth interviews, observations (careful responses at the pure sensory level), and documentation studies and, data analysis techniques using the Miles and Huberman namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that; The polarization system for internal proselytizing for the coastal core families is carried out during the conception and birth period by welcoming the call to prayer and qamat, and then singing the song Yabe Lale, Salawat Badr, as a motivation for life, aqiqah, and teaching prayer, being honest.